A compreensão do sofrimento no escalpelamento: um estudo utilizando o grafismo e o teste das fábulas - VALE, Jesiane Calderaro Costa (2007)
Studies on scalpel events have been very scant. Very few are to be found in the areas of medicine, occupational therapy and physiotherapy. The existing studies give priority to the physical, organic and corporal aspects of the event. In this paper, we study the scalpel event under the perspective of Psychology; focusing, on the psychological suffering and its expression. For this purpose we have used clinically qualitative methods. We have elected two projective instruments as well: The Fables Test according to Düss, and drawings of the human body. The research took place in the Santa Casa de Misericórdia Foundation in the city of Belém, Pará in Brazil. Two patients, victims of scalpel events, were contacted as participants. The criteria for their selection, was the following: that the event occurred more than six months ago; that they be no longer in the hospital; that they presented physical and psychological conditions to take part; and that their parents authorized their participation in this study. We concluded, that the psychological suffering manifested by the victims, cannot be denied. They suffered a tragedy, but the impact of this scalpel event proved to be an unprecedented experience, unquestionably subjective and markedly singular in nature. In sight of this problem, we verified that it was not only ones body that suffered the pain, but their psychological being as well. We highlight the use of the referred instruments as favorable resources of expressing this pain.